PROJECT PROPOSALS FOR THE LOCATION OF MODERN PARKS IN THE RESIDENTIAL AREA - Nazari Abdulbasir; Turaev Khumoyiddin Abdugafforovich (Research Parks Publishers, 2021)
This article discusses the methodology of creating a modern design of a car park with the help of graphic programs, as well as project proposals for the placement of modern car parks in the residential area.